1996
DOI: 10.1088/0957-0233/7/8/011
|View full text |Cite
|
Sign up to set email alerts
|

Void fraction measurements in gas - liquid flows using capacitance sensors

Abstract: Void fraction measurements for vertical flow in a small diameter tube (9.53 mm) were taken using two non-intrusive capacitive void fraction sensors. The sensors were needed to measure the void fraction of water-air two-phase flow under normal gravity and microgravity conditions. Void fraction data were collected with: (1) a sensor having helical wound electrodes that was used to collect data under normal gravity and microgravity conditions, (2) a sensor having concave plate electrodes, used to collect data at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…Aluminum was selected for its machinability, high corrosion resistance and relatively low cost. The two cylindrical probes were made to have equal lengths to eliminate non-uniformity in the sensing electric field [Elkow and Rezkallah, 1996]. The length and the diameter of the two cylindrical probes were selected to minimise three-dimensional effects.…”
Section: Description Of the Two-cylinder Capacitance Ice Sensormentioning
confidence: 99%
“…Aluminum was selected for its machinability, high corrosion resistance and relatively low cost. The two cylindrical probes were made to have equal lengths to eliminate non-uniformity in the sensing electric field [Elkow and Rezkallah, 1996]. The length and the diameter of the two cylindrical probes were selected to minimise three-dimensional effects.…”
Section: Description Of the Two-cylinder Capacitance Ice Sensormentioning
confidence: 99%
“…Capacitance sensors for instantaneous void fraction in air-oil, two-phase flow were developed [74][75][76]. This method could effectively identify the different flow regimes although it was not effective while there was high water loading.…”
Section: Advanced Void Fraction Measurement Techniquesmentioning
confidence: 99%
“…Helical electrodes were found to have low sensitivity, non-linear response and poor shielding [11]. On the other hand, ring and concave type electrodes have linear relationship between void fraction and capacitance value [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ring and concave type electrodes have linear relationship between void fraction and capacitance value [10]. It was also found that concave electrodes have higher sensitivity than both the ring and helical [11][12]. There are several capacitance measuring techniques which can be used to measure the capacitance sensor.…”
Section: Introductionmentioning
confidence: 99%